Rapid cell surface appearance of endocytic membrane proteins in Chinese hamster ovary cells. - Storrie, B (Mol Cell Biol, 1981)
Lactoperoxidase was used to selectively radiolabel endocytic membrane. CHO cells were incubated with enzyme at 37 degrees C for 10 min to permit lactoperoxidase internalization. Radioiodination was done at 4 degrees C. About 90% of the radioiodinated products pelleted at 100,000 X g. From 12 to 15 different electrophoretic species were detected by one-dimensional gel electrophoresis. When cells labeled by internalized lactoperoxidase were warmed to 37 degrees C, the incorporated radioactivity was lost in a biphasic manner with an overall t1/2 of approximately 20 h. Upon warming cells to 37 degrees C, the labeled species became sensitive to pronase or trypsin digestion. The increase in protease sensitivity was progressive over a 10- to 20-min period. Maximally 45% of the initially intracellular radiolabel could be released. A digest of exterior-radioiodinated cells released 50% of the incorporated radioiodine. These observations strongly suggest a rapid shuttling of approximately 90% of the radioiodinated membrane species initially present within the cell to the cell surface.